Formal job, informality and unemplyment in Brazil post Labor Reform (law 13467/2017) (Research, Society and Development, 2021)
Law 1347/2017 instituted Labor Reform in Brazil altering Consolidation of Labor Laws (Consolidação das leis do trabalho – CLT), decree-law 5452/1993, main legislative instrument of labor regulation in the country. The Reform was approved under government justification, form the need of modernizing and loosening rules contained in CLT, aiming to increase formal jobs creation with signed labor, to reduce informal job taxes and foment economics. This article aims to analyse governmental indexes of unemplyment , formal and informal job in the country after Labor Reform, so to verify if the alteration in legislation effectively fulfilled its purpose, reduced unemployment and informality and it raised the number of hiring with signed labor. To this research fulfillment, decriptive method of integrative review was used in literature from articles published in international and reputed national journals, works from law and economics authors and governmental statistic data analysis about unemployment and informality, colected in 2016, a year before implementation of law 13467/17 and on 20th february, month that preceeded Covid 19 pandemic in Brazil. Results found indicated that flexibilization broughty by the Reform contributed just a little to formal job generation and to reduce unemployment, there was a raise of informality indexes in the researched period and elevation of poverty and extreme poverty in Brazil.